Uji Toksisitas Oral Akut Single Dose Filtrat Buah Luwingan (Ficus hispida L.f.) pada Tikus (Rattus norvegicus Berkenhout, 1769) Galur Wistar - Laksmindra Fitria (Mangifera Edu, 2019)
Genus Ficus is important plant for health benefits. Hairy fig (F. hispida) trees grow abundantly in tropical regions and fruiting throughout the year. In West Asian countries, the fruit is commonly used as food and medicinal materials. However, in Indonesia, the fruit has not been utilized. First step in exploring the potential of natural resources for consumption is toxicity test to provide information about safety and adverse effects. This research was aimed to study acute oral toxicity of young and ripe hairy fig fruits using Wistar rats as model. Procedure followed OECD Guideline Test No.420 with modification. Pure filtrate (100 %) of young or ripe fruits were administered orally at volume 1 mL/individual on day-0 in fasting animals. Control received distilled water in the same way. Parameters observed including mortality, sublethal effects, behavior/activities, body weight, complete blood count, as well as evaluation of liver, heart, and renal functions. Results showed that values for all variables fluctuated during the experiment but eventually back into normal range. However, the number of lymphocytes elevated until the end of experiment (day-14) thus increased the total leukocytes count. Accordingly, we are preparing to conduct further toxicity tests to investigate this finding. Key words : acute oral toxicity, Ficus hispida, fruit filtrate, hairy fig, single dose toxicity